Avaliação do desgaste promovido pela broca post preparation utilizando imagens de TCCB - Cibin, Francielli Weber Santos (2005)
Several metals are known to disturb cellular functions by binding to thiol groups of biomolecules. Therefore, a possible therapy for metal intoxication is to remove the toxic metals from the bound functional bioligands by administering strong thiol-containing chelators. However, these compounds could remove endogenous metals, which are essential components of many enzyme systems. Thus, the present study was designed to evaluate the effects of chelating agents, meso-2,3-dimercaptosuccinic acid (DMSA), 2,3-dimercaptopropane 1-sulfonate (DMPS) and 2,3-dimercaptopropanol (BAL) per se on toxicological parameters and models of cadmium intoxication. δ-Aminolevulinate dehydratase (δ-ALA-D) activity from human erythrocytes was inhibited by dithiol chelating agents in a concentration-dependent manner. Dithiotreitol and zinc chloride were able to protect the δ-ALA-D inhibition caused by BAL, DMPS and DMSA in a concentration-dependent manner. Acute treatment with chelating agents caused changes in a number of toxicological parameters in mice. BAL caused a decrease on renal δ-ALA-D activity and an increase on brain and liver enzyme activity. DMPS caused an inhibition in renal δ-ALA-D activity, while animals that received a single dose of DMSA did not present δ-ALA-D activity of tissues modified. All three agents produced an increase in both liver and renal lipid peroxidation. Mice that received DMPS presented an increase in renal zinc concentration and a depletion of hepatic zinc occurred in mice administrated with BAL. Of all the toxic metals found in the environment and used in industry, cadmium occupies a special place because of the generally intractable nature of cadmium intoxication. Several lines of evidence indicate that reactive oxygen species are involved in cadmium-mediated tissue damage. Thus, it is believed that antioxidant should be one of the important components of an effective treatment of cadmium poisoning, as well, combined therapy with antioxidants and chelators can yield better therapeutic outcomes than isolated chelation therapy. Acute cadmium-intoxication caused inhibition of δ-ALA-D and superoxide dismutase (SOD) activities, reduction in ascorbic acid levels and increase of lipid peroxidation in mice testes. Also, an increase on plasmatic lactate dehydrogenase (LDH), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities was observed. DMSA, DMPS and diphenyl diselenide ((PhSe)2) protected against the inhibitory effect of cadmium on δ-ALA-D activity and restored the increase of TBARS levels. However, these compounds alone or in combination, were unable to protect SOD activity and to improve ascorbic acid levels near to the normal value. The use of combined therapy (DMSA plus (PhSe)2) not proved be better than the monotherapy, in improving the toxicological parameters evaluated in this model of testicular damage induced by cadmium. On the other hand, the use of combined therapy (DMPS plus (PhSe)2) proved to be better than the monotherapy in decreasing cadmium levels in testes and in ameliorating plasmatic AST level. Sub-chronic effects of cadmium-intoxication in mice caused inhibition of δ-ALA-D activity in liver, kidney and spleen and (PhSe)2 therapy was effective in restoring enzyme activity in all tissues. Also, a reduction in ascorbic acid content by cadmium was observed in kidney and spleen, whereas (PhSe)2 was only effective in improving this reduction in kidney. The therapy with this compound was effective in restoring an increase of TBARS levels caused by cadmium in liver and brain tissues. In general, the results of this study indicate that it is necessary to investigate the potential toxicity of the chelating agents, since chelators may be as harmful as the metals they chelate. In addition, (PhSe)2 therapy in cadmium poisoning may be considered, as alone (antioxidant) as combined with DMPS and DMSA